Peran Guru dalam Upaya Meningkatkan Keaktifan Siswa dalam Kelas - Alfin Nur Hidayat; Anastasia Putri Agung Febriana; Aprilia Ayu Nurcahyani; Endrise Septina Rawanoko (International Forum of Researchers and Lecturers, 2024)
The role of teachers in enhancing students' active participation in the learning process, which is considered an important element in the success of teaching and learning activities. This study applies a descriptive qualitative approach and literature review to recognise the various elements that impact on student participation, including internal (psychological and physiological) and external (non-social and social) factors. The article also examines learning strategies such as problem-oriented learning, active learning and project-based learning to enhance student engagement. In addition, methods such as ‘Index Card Match’ and discovery-based learning models are used to increase student participation. The results showed that students' participation contributed significantly to their learning achievement, both through active involvement in discussions and the courage to ask questions. The author suggests the application of creative teaching methods as well as efficient teacher questioning skills to optimise students' participation potential in the classroom.